Types and prevalence of adverse skin reactions associated with prolonged N95 and simple mask usage during the COVID‐19 pandemic. (6th July 2022) - Darnall, A.R.; Sall, D.; Bay, C.
Abstract: Background: As the coronavirus 2019 (COVID‐19) pandemic persists on a global level, the chronic daily use of face masks within the healthcare system remains an important component of disease prevention and transmission. Increased use of personal protective equipment (PPE) may result in increased rates of occupational dermatoses and adverse skin reactions. Objectives: The purpose of this study is to explore how chronic, prolonged use of N95 masks or simple surgical masks affects the prevalence of adverse skin reactions in Healthcare Workers (HCWs). Methods: An optional, quantitative, web‐based survey was administered to patient‐facing HCWs across six network hospitals in a large metropolitan city. Data were analysed to assess the types and sites of adverse skin reactions, and to evaluate correlations between single mask use duration and adverse skin reactions. Results: A total of 230 HCWs responded with 192 endorsing occupational dermatoses. Among the healthcare responders, ( n  = 192, 83.5%) experienced at least one adverse skin reaction. The most common occupational adverse skin reactions were acne ( n  = 133, 57.8%), dryness ( n  = 108, 47.0%) and redness ( n  = 105, 45.7%). Anatomical areas most commonly affected included the nasal bridge ( n  = 92, 40.0%), cheeks ( n  = 92, 40.0%) and chin ( n  = 91, 39.6%). Acne ( P  = 0.002), dryness/scaling ( P  = 0.002), increased pore size (0.003), itch ( P  = 0.003), nasal bridge scarring ( P  < 0.001), redness ( P  < 0.001), frictional erosions ( P  = 0.001) and ulcerations ( P  = 0.002) showed a positive correlation to duration of mask use. Conclusions: Prolonged, daily usage of PPE is associated with numerous adverse skin reactions among HCWs with acne being the most commonly seen adverse reaction. Many adverse reactions are associated with prolonged use of single mask.